Does vitamin D supplementation improve bone health, body composition and physical performance beyond endurance exercise in patients with type 2 diabetes: A secondary analysis of randomized controlled trial - Sun, Xiaomin; Xiao, Wenjuan; Li, Zhongying; Zhou, Sirui; Dong, Mengyue; Huang, Cong; Ma, Yan; Gou, Bo (Frontiers in Physiology, 2022)
This study aimed to assess the effects of a 12-week vitamin D and endurance exercise intervention on bone health, body composition and physical performance among patients with type 2 diabetes mellitus (T2DM). Totally, 61 patients with T2DM were randomly assigned to vitamin D supple-mentation group (VDG, 1000 IU/day), exercise training group (EG), vitamin D and exercise in-tervention group (VEG), and control group (CG). Bone health (bone mineral density, BMD; bone mineral content, BMC), body composition and physical performance were measured before and after the intervention. Dual energy X-ray absorptiometry was used to assess bone health and body composition. Significant vitamin D main effects on total BMC, trunk BMC, and spine BMD were observed (VDG + VEG vs. EG + CG, 95% confidence interval [CI]: −29.9, 19.4 vs. −74.9, −24.7; −24.1, 19.5 vs. −56.1, −11.7; −0.03, 0.03 vs. −0.07, −0.01), although there were no significant inter-active effects. Patients in EX had a decreased BMC, while it was alleviated in VEG after inter-vention. Exercise had a main effect on the reduction of total and trunk BF%. Although no additive effect of vitamin D supplementation beyond exercise training, the supplementation had a po-tential effect on the prevention of bone loss induced by exercise.